3D printing of Osage orange extract/Chitosan scaffolds for soft tissue engineering - Elif Saatcioglu (Elsevier, 2021)
In this study, three-dimensional tissue scaffolds were fabricated using a 3D printing process. Chitosan (CS) was used as a matrix polymer, and Osage orange extract (OGE) with different amounts was added as a bioactive material. The scaffolds were characterized by SEM, FTIR, tensile testing, antibacterial, and biocompatibility tests. The SEM images revealed that scaffolds had homogeneous morphology, and the size of the pores ranged from 160 µm to 270 µm. FTIR spectrum of the extracted Osage Orange confirmed the successful extraction of the Osage Orange. The OGE addition decreased the swelling capacity of the CS scaffold proportionally. Biocompatibility results proved the biostability properties of the scaffolds. According to the results, the antibacterial activity of the scaffolds against the Staphylococcus Aureus (S. aureus) and Enterococcus Faecalis (E. faecalis) should be provided after detailed optimization.